1981
DOI: 10.1139/y81-087
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of acetylcholine receptor and acetylcholinesterase metabolism by actinomycin D In cultured muscle cells

Abstract: Actinomycin D (ACT-D), an inhibitor of transcription, was added to chick muscle cultures to study its effect on the synthesis of acetylcholine receptor (ACHR) and acetylcholinesterase (ACHE, EC 3.1.1.7). Doses of ACT-D (1.85-18.5 nM), which inhibited uridine incorporation up to 80%, increased ACHR, ACHE, and creatine kinase (CK, EC 2.7.3.2) levels without affecting general cell protein. Degradation of ACHR was slower in ACT-D treated cultures than controls, resulting in a twofold increase in receptor half-life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This has been supposed to be due to a decreased Na + -K + -ATPase activity during these days. It was observed that the degradation of the acetylcholine receptor was slow in ACT-D-treated muscle culture cells, resulting in a twofold increase in receptor half-life [38]; any change in the rate of AChE secretion was accompanied by an identical change in the rate of acetylcholine receptor incorporation into the plasma membrane [39]. Moreover, increased intracellular cAMP levels, as observed in CHX-plus-PTU-treated rats, may facilitate the release of acetylcholine [40], resulting in an increased activity of AChE to metabolize acetylcholine.…”
Section: Discussionmentioning
confidence: 99%
“…This has been supposed to be due to a decreased Na + -K + -ATPase activity during these days. It was observed that the degradation of the acetylcholine receptor was slow in ACT-D-treated muscle culture cells, resulting in a twofold increase in receptor half-life [38]; any change in the rate of AChE secretion was accompanied by an identical change in the rate of acetylcholine receptor incorporation into the plasma membrane [39]. Moreover, increased intracellular cAMP levels, as observed in CHX-plus-PTU-treated rats, may facilitate the release of acetylcholine [40], resulting in an increased activity of AChE to metabolize acetylcholine.…”
Section: Discussionmentioning
confidence: 99%